A strategy on generating structured plateau surface by the sinusoidal oscillatory lapping of the grinding wheel with the phyllotactic pattern of abrasive grains. (May 2021) - Lyu, Yushan; Liu, Yueming; Li, Xingshan; Di, Hanxu; Wang, Hai
Abstract: The structured plateau surface can reduce the contact friction force on workpiece surfaces based on the kinematics principle of superfinishing considering the phyllotaxis theory of biology. In this paper, the strategy on lapping structured platform surface over cyclindrical component has been proposed with the help of the sinusoidal movement of ordered grinding wheel. In order to achieve this strategy, the lapping device has been first designed and manufactured, and the design theory of ordered grinding wheel is given. The ordered grinding wheel is manufactured, and then the equation of the lapping trajectory of abrasive particles is established while considering processing parameters. The kinematic conditions of generating structured plateau surface is discussed, and the geometric generating mechanism of the plateau surface is analyzed by means of the trajectory simulation results. Finally the problems related to the lapping process and the generating mechanism of the plateau surface are analyzed and discussed based on the experimental investigation results. The research results show that the sinusoidal oscillation lapping of the order grinding wheels which are arranged according to whorls, staggered whorls and spiral pattern, can generate different structured plateau surface. The geometry shape of the plateau surface and its consistency depend on the configuration form and parameters of the grinding wheel.